Single cell analysis of the localization of the hematopoietic stem cells within the bone marrow architecture identifies niche-specific proliferation dynamics - Mazzarini, Maria; Arciprete, Francesca; Picconi, Orietta; Valeri, Mauro; Verachi, Paola; Martelli, Fabrizio; Migliaccio, Anna Rita; Falchi, Mario; Zingariello, Maria (Frontiers in Medicine, 2023)
Introduction Hematopoietic stem cells (HSC) reside in the bone marrow (BM) in specialized niches which provide support for their self-replication and differentiation into the blood cells. Recently, numerous studies using sophisticated molecular and microscopic technology have provided snap-shots information on the identity of the BM niches in mice. In adults, HSC are localized around arterioles and sinusoids/venules whereas in juvenile mice they are in close to the osteoblasts. However, although it is well recognized that in mice the nature of the hematopoietic niche change with age or after exposure to inflammatory insults, much work remains to be done to identify changes occurring under these conditions. The dynamic changes occurring in niche/HSC interactions as HSC enter into cycle are also poorly defined. Methods We exploit mice harboring the hCD34tTA/Tet-O-H2BGFP transgene to establish the feasibility to assess interactions of the HSC with their niche as they cycle. In this model, H2BGFP expression is driven by the TET trans-activator under the control of the human CD34 promoter which in mice is active only in the HSC. Since Doxycycline inhibits TET, HSC exposed to this drug no longer express H2BGFP and loose half of their label every division allowing establishing the dynamics of their first 1-3 divisions. To this aim, we first validated user-friendly confocal microscopy methods to determine HSC divisions by hemi-decrement changes in levels of GFP expression. We then tracked the interaction occurring in old mice between the HSC and their niche during the first HSC divisions. Results We determined that in old mice, most of the HSC are located around vessels, both arterioles which sustain quiescence and self-replication, and venules/sinusoids, which sustain differentiation. After just 1 week of exposure to Doxycycline, great numbers of the HSC around the venules lost most of their GFP label, indicating that they had cycled. By contrast, the few HSC surrounding the arterioles retained maximal levels of GFP expression, indicating that they are either dormant or cycle at very low rates. Conclusion These results reveal that in old mice, HSC cycle very dynamically and are biased toward interactions with the niche that instructs them to differentiate.